Dasatinib suppresses particulate-induced pyroptosis and acute lung inflammation - Pan, Yixi; Ikoma, Kenta; Matsui, Risa; Nakayama, Akiyoshi; Takemura, Naoki; Saitoh, Tatsuya (Frontiers in Pharmacology, 2023)
Background: Humans are constantly exposed to various industrial, environmental, and endogenous particulates that result in inflammatory diseases. After being engulfed by immune cells, viz. macrophages, such particulates lead to phagolysosomal dysfunction, eventually inducing pyroptosis, a form of cell death accompanied by the release of inflammatory mediators, including members of the interleukin (IL)-1 family. Phagolysosomal dysfunction results in the activation of the nod-like receptor family pyrin domain containing 3 (NLRP3) inflammasome, an immune complex that induces pyroptosis upon exposure to various external stimuli. However, several particulates induce pyroptosis even if the NLRP3 inflammasome is inhibited; this indicates that such inhibition is not always effective in treating diseases induced by particulates. Therefore, discovery of drugs suppressing particulate-induced NLRP3-independent pyroptosis is warranted. We screened compounds that inhibit silica particle (SP)-induced cell death and release of IL-1α using RAW264.7 cells, which are incapable of NLRP3 inflammasome formation. The candidates were tested for their ability to suppress particulate-induced pyroptosis and phagolysosomal dysfunction using mouse primary macrophages and alleviate SP-induced NLRP3-independent lung inflammation. Results: Several Src family kinase inhibitors, including dasatinib, effectively suppressed SP-induced cell death and IL-1α release. Furthermore, dasatinib suppressed pyroptosis induced by other particulates but did not suppress that induced by non-particulates, such as adenosine triphosphate. Dasatinib reduced SP-induced phagolysosomal dysfunction without affecting phagocytosis of SPs. Moreover, dasatinib treatment strongly suppressed the increase in IL-1α levels and neutrophil counts in the lungs after intratracheal SP administration. Dasatinib suppresses particulate-induced pyroptosis and can be used to treat relevant inflammatory diseases.